Sustainability implementation and certification challenges in the Arctic operating environment : the case of Salla's tourism businesses - Johnson, Carla Rose (2024)
Implementing sustainability strategy through sustainability certifications and ecolabelling have become increasingly popular for tourism businesses, especially in Finland with the popularity of the Green Key Certificate and the Sustainable Travel Finland (STF) Label. These sustainability standards have strict criteria that must be fulfilled to achieve these certificates and labels. Tourism businesses in Salla have suggested that the Arctic operating environment presents increased challenges on achieving sustainability implementation. The aim of this thesis was to discover and assess how the Arctic operating environment is affecting Salla’s tourism businesses’ ability to achieve the sustainability criteria laid out by these sustainability standards, providing suggestions for further research and development. The theoretical framework was divided into 3 sections, The Arctic operating environment in Finnish Lapland, Sustainable tourism, and certification and labelling. A qualitative case study approach was conducted, focused on the Salla tourism industry, with a method of semi-structured interviews with business owners who have achieved both the STF Label and the Green Key Certificate plus a representative from the Municipality of Salla. Analysis was conducted by transcription, content analysis, coding, clustering and thematic generation. The main results revealed that the biggest challenges that the Arctic operating environment presents to sustainability implementation in Salla was distances and freezing temperatures, effecting both the tourism businesses’ carbon footprint and energy efficiency. These challenges had operational impacts for these businesses but did not objectively prevent businesses from achieving the criteria needed for these standards. These standards remain relevant for the Arctic regions, but this is mostly due to the presence of a process-based approach, improving by a set amount periodically, typically on a yearly basis. The tourism businesses in Salla placed an emphasis on co-operation and ...